The Effectiveness of Teams Games Tournament (TGT) Cooperative Learning in Enhancing Fiqh Learning Outcomes among Islamic Junior Secondary Students - Fitri Maulina (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
The effectiveness of instructional strategies in improving students’ learning outcomes remains a major concern in Islamic Religious Education, particularly in Fiqh learning, where conventional teacher-centered approaches often limit student engagement and participation. This study aimed to examine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in enhancing Fiqh learning outcomes among Islamic junior secondary school students. The study employed a quantitative approach using a one-group pretest–posttest quasi-experimental design. The participants consisted of 18 second-grade students of MTsS Darul Kiram during the 2024–2025 academic year. Data were collected through multiple-choice tests measuring students’ learning outcomes and a student response questionnaire. The collected data were analyzed using descriptive statistics, a paired-samples t-test, N-Gain analysis, and effect size calculations. The findings revealed a substantial improvement in students’ academic achievement following the implementation of the TGT model. The mean pretest score increased from 63.89 to 90.00 in the posttest. The paired-samples t-test indicated a statistically significant difference between pretest and posttest scores (t = -28.86, p < 0.001), while the N-Gain value of 0.72 was categorized as high, indicating meaningful learning improvement. Furthermore, the effect size analysis demonstrated a very large educational impact of the intervention. Student perceptions of the learning experience were highly positive, with an average response rate of 98.11%, suggesting increased motivation, engagement, and enjoyment during the learning process. The novelty of this study lies in providing empirical evidence on the effectiveness of TGT within the context of Fiqh education at the Islamic junior secondary level, an area that remains underexplored in international educational research. This study contributes to the growing literature on cooperative and game-based learning by demonstrating that TGT can serve as an effective pedagogical strategy for improving learning outcomes and fostering active student participation in Islamic education.